Suicides and accidents on birthdays: Evidence from Japan. (June 2016) - Matsubayashi, Tetsuya; Ueda, Michiko
Abstract: This study examined whether people have a higher risk of death on and around their birthday using a large national mortality data. We examined 2, 073, 656 death records of individuals who died in Japan from major external causes between 1974 and 2014. Poisson regression analysis showed that people were more likely to die on their birthday than on any other calendar day by means of suicide, traffic accidents, accidental falls, drowning, and choking. For suicide cases in particular, people are 50% more likely to die on their birthday compared to any other dates. Excess deaths on birthdays were observed regardless of gender, marital status, and age-at-death subgroups. For suicide deaths, our results provided strong support for the "birthday blues" hypothesis that predicts excess deaths on birthdays. With regards to traffic accidents and other unintentional accidents, however, our results suggest that excess deaths on birthdays may be related to birthday celebrations. For the elderly population, our analysis indicates that special activities associated with birthday celebrations, which often involves going out to consume festive food and drinks, may be contributors to a sudden increase in the number of accidental deaths on their birthday. In contrast, a notably sharp increase in the number of motor vehicle accidents was observed for individuals in the 20s on their birthday, which may be attributable to birthday celebrations that involved both driving and drinking. Highlights: People are more likely to die on their birthday compared to any other dates. The number of deaths by suicide is particularly high on birthdays. The number of deaths by unintentional accidents is also high on birthdays. The "birthday blues" hypothesis was supported by data for suicide deaths. Excess deaths on birthdays by accidents may be related to birthday celebrations.